Die verwysing van hupèr eléous in Romeine 15:9 - Engelbrecht, E. (Hervormde teologiese studies, 1986)
The reference of hupèr eléous in Romans 15:9 The question of how hupèr eléous is to be understood in Romans 15:9 is answered with two presuppositions in mind. The letter to the Romans is understood as a paranetic reminder which culminates in 15:7-13. Furthermore it is argued that the context of this passage is the letter itself rather than a Pauline theology. The microstructure of the term is investigated to determine the resiprocal interrelationship between the term and its immediate neighbourhood. These results are used to control the presuppositions relating to the macro-context. The term hupèr eléous functions within the idea that Christ's acceptance of the congregation is coordinated by God's truthfulness towards Israel and his mercy towards the gentiles. This mercy of God is a new and surprising act of God, but since this mercy of God is Christ's acceptance of the gentiles, it is related to God's truthfulness to Israel which was manifested in Christ's confirmation of the promises given to the patriarchs. This has implications for the interrelationship between the church and the Jews.